Key Performance Indicators in Brazilian Software Development Companies: a Survey - Alexandre, Mariana; OliveiraJr, Edson; Carvalho, Ana Paula M.; Colanzi, Thelma E.; Balancieri, Renato (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
This paper addresses the importance of Key Performance Indicators (KPIs) in software development management. These indicators are quantitative and qualitative metrics that help measure, monitor, and evaluate the performance and quality of the software development process. The objective of the study is to identify which KPIs are most commonly used by companies, understand how these indicators positively impact the work of development teams, and analyze the challenges faced in their implementation. The research was conducted through an online survey, collecting data from 13 participants. The results showed that all participants were familiar with KPIs, and most had received adequate training on their use. The most mentioned KPIs were Bug Control, Failure Rate, Impediments, Cycle Time, and Lead Time. The benefits observed included improved communication, increased productivity, and identification of technical bottlenecks. However, participants also highlighted challenges such as process interruptions when expectations are not met and cultural differences. In conclusion, the study indicates that the use of KPIs contributes to improving software development processes and benefits project management. Nevertheless, KPIs must be implemented gradually and continuously monitored to overcome challenges and maximize their benefits.